Antibiotic Prescribing Rate in Lebanese Community Pharmacies: A Nationwide Patient-Simulated Study of Acute Bacterial Rhinosinusitis - Sally G. Yaacoub; Nathalie A. Lahoud; Nicole J. Francis; Deema W. Rahme; Tony H. Murr; Patrick F. Maison; Nadine G. Saleh (Springer, 2019)
This study aims to evaluate the antibiotic prescribing rate for acute bacterial rhinosinusitis in community pharmacies and to study the corresponding attitude and behavior of participants. A cross-sectional, nationwide study was conducted using a patient-simulated case of bacterial rhinosinusitis. Descriptive data were reported for the medications prescribed, questions asked, and recommendations made. Bivariate analysis was conducted to identify factors affecting the aforementioned. Out of the 250 community pharmacies visited, 77 (30.8%) prescribed antibiotics, 15 (6%) referred the patient to a physician, and 79 (32%) made the right diagnosis. Amoxicillin/clavulanic acid (69.7%) was the most prescribed antibiotic. The majority of the participants prescribed antibiotics according to guidelines. Overall, 108 (43.2%) participants questioned about symptoms and few questioned about patient age, pregnancy, and history of rhinosinusitis. None counseled about interactions or in case a dose is missed. We concluded that antibiotics are easily prescribed in Lebanese community pharmacies. This misuse should be tackled by legislative authorities to restrict such practices.